2014
DOI: 10.1111/ajt.12927
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Normothermic Regional Perfusion for Controlled Donation After Circulatory Death—The United Kingdom Experience

Abstract: Organs recovered from donors after circulatory death (DCD) suffer warm ischemia before cold storage which may prejudice graft survival and result in a greater risk of complications after transplant. A period of normothermic regional perfusion (NRP) in the donor may reverse these effects and improve organ function. Twenty-one NRP retrievals from Maastricht category III DCD donors were performed at three UK centers. NRP was established postasystole via aortic and caval cannulation and maintained for 2 h. Blood g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
287
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(305 citation statements)
references
References 26 publications
5
287
3
5
Order By: Relevance
“…On the basis of this, starting normothermic perfusion already in donors may lead to different results. 33,34 Furthermore, we cannot exclude that perfusion for >1 hour would have been more effective (warm and cold).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of this, starting normothermic perfusion already in donors may lead to different results. 33,34 Furthermore, we cannot exclude that perfusion for >1 hour would have been more effective (warm and cold).…”
Section: Discussionmentioning
confidence: 99%
“…47 Different thermic regional perfusion techniques show promise; when studied in organs donated after circulatory death, normothermic regional perfusion, in particular, has considerable potential to restore the quality of these grafts. 43 Oniscu et al 48 also demonstrated a low occurrence of DGF (40%) when normothermic regional perfusion was used. When looking at clinical practice, we see that machine reperfusion is being used, especially in centers that have ongoing ECD programs.…”
Section: Early Ischemic Injury and Dgf In Kidney Transplantationmentioning
confidence: 93%
“…Furthermore, cannulation was implemented postmortem, which also increased WIT. Oniscou et al reported 40% incidence of DGF in 32 renal grafts with ECMO and 12.5% incidence of PNF (12). In this U.K. protocol, cannulation was implemented postmortem after sternotomy, and thus WIT was prolonged.…”
Section: Does the Use Of Ecmo In Cdcdd Programsmentioning
confidence: 99%
“…Description of cDCDD protocols using ECMO and an aortic clamp In the United Kingdom, three centers (Cambridge, Birmingham, and Edinburgh) recently developed another procedure using ECMO, called normothermic regional perfusion (NRP) (12). After W-LST occurs either in the intensive care unit (ICU) or in the OR, death is determined after a notouch period of 5 min.…”
Section: Consentmentioning
confidence: 99%
See 1 more Smart Citation